For a Critique of Philosophical Archeology. A review of Giorgio Agamben’s “Homo sacer” - Raciti, Andrea (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
In this review of Giorgio Agamben’s Homo sacer. Edizione integrale. 1995-2015, the main theme is the critique of the philosophical method used by the Italian philosopher. The method is called “philosophical archaeology”. It could be considered a particular research finalized to demonstrate the structure of western politics as a “double machine”: animal life – the Aristotelian zoe – in the origin of the western political and metaphysical thought is excluded and included in polis at the same time, a kind of hidden foundation opposed and linked with political life – the Aristotelian bios. In this review are analyzed new possible horizons opened thanks to this method, but also its aporias and contradictions. Keywords: Power, Form of Life, Exception, Signature, Inoperosity.